ONLINE TRANSPORTATION BUSINESS TAX COMPLIANCE - Ardhiatul Halima Tuasalamony; Fadlia Nasaruddin; Tenriwaru Tenriwaru (Universitas Islam Balitar, 2020)
This study aims to determine how the compliance of online transportation business taxpayers in fulfilling tax obligations as taxpayers at the Pratama West Makassar Tax Office (KPP). The basis of this research is a qualitative descriptive type of research. The analytical method used in this study refers to the steps proposed by Miles and Huberman. Data obtained from the results of this study through semi-structured interviews and documentation. Informants in this study were employees of Pratama Tax Office (KPP) West Makassar and several online transportation partners / drivers. The results show that not all online transportation partners / drivers understand tax reporting procedures properly, the efforts of Pratama Tax Office (KPP) West Makassar to minimize the obstacles that occur, by socializing taxation either directly or through social media or online. Another problem that arises is that there are no specific regulations governing the online transportation business classification (KLU) itself. So it is difficult to detect tax compliance of online transportation business taxpayers.